PENGARUH NILAI PH TANAH TERHADAP POTENSI PENGGUNAAN LAHAN PERTANIAN SECANGGANG KABUPATEN LANGKAT - Adhyaksa, Yohannes; Hasibuan, Mahidin EL Wafa; Apriansyah Sembiring; Izhar Hasan Nasution; Dwi Mutia Anggraini; Saragih, Sri Wahyuna; Lubis, Rosliana; Sigit; Meliala, Bibel Agrivino (Institut Teknologi Sawit Indonesia (ITSI), 2025)
This study aims to determine soil pH values using various dilution levels with water (H₂O) and 1 N KCl solution, and to analyze their effects on soil acidity and its implications for soil fertility. Soil pH is an important indicator that influences nutrient availability and plant growth, particularly in oil palm cultivation. The research was conducted in an ITSI Soil Laboratory by mixing air-dried soil with H₂O and KCl in ratios of 1:1 and 1:2.5. The results showed that soil pH mixed with water ranged from 5.3 to 5.8 (slightly acidic), while soil mixed with 1 N KCl had lower pH values, ranging from 4.2 to 4.4 (strongly acidic). The decrease in pH when using KCl solution is due to the exchange of H⁺ and Al³⁺ ions from soil colloids into the solution, resulting in increased soil acidity. This condition can reduce nutrient availability, suppress microbial activity, and potentially lead to toxicity in plants if not properly managed. Therefore, soil pH management through liming is necessary to achieve optimal conditions for plant growth.